2021
DOI: 10.3390/ijms22073797
|View full text |Cite
|
Sign up to set email alerts
|

Combining Magnetic Resonance Imaging with Systemic Monocyte Evaluation for the Implementation of GBM Management

Abstract: Magnetic resonance imaging (MRI) is the gold standard for glioblastoma (GBM) patient evaluation. Additional non-invasive diagnostic modalities are needed. GBM is heavily infiltrated with tumor-associated macrophages (TAMs) that can be found in peripheral blood. FKBP51s supports alternative-macrophage polarization. Herein, we assessed FKBP51s expression in circulating monocytes from 14 GBM patients. The M2 monocyte phenotype was investigated by qPCR and flow cytometry using antibodies against PD-L1, CD163, FKBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In this setting the numbers of these circulating M2-like monocytes are not only significantly increased relative to those of healthy control subjects and patients with benign disease ( 49 , 50 ), but are also metabolically quiescent, displaying transcriptomes on activation that reflect decreased expression of gene sets involved in oxidative phosphorylation, fatty acid metabolism, and inner mitochondrial membrane protein complex ( 49 ). A similar association between an intra-tumoral and systemic predominance of M2-like macrophages/monocytes associated with a poor prognosis has also been described in glioma/glioblastoma patients ( 51 , 52 ).…”
Section: Discussionsupporting
confidence: 71%
“…In this setting the numbers of these circulating M2-like monocytes are not only significantly increased relative to those of healthy control subjects and patients with benign disease ( 49 , 50 ), but are also metabolically quiescent, displaying transcriptomes on activation that reflect decreased expression of gene sets involved in oxidative phosphorylation, fatty acid metabolism, and inner mitochondrial membrane protein complex ( 49 ). A similar association between an intra-tumoral and systemic predominance of M2-like macrophages/monocytes associated with a poor prognosis has also been described in glioma/glioblastoma patients ( 51 , 52 ).…”
Section: Discussionsupporting
confidence: 71%
“…Giordano et al found that DTI imaging technology has characteristics of brain endoplasmic injury in toxic encephalopathy. Compared with the control group, FA in the corpus callosum and corpus callosum decreased significantly [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Importantly, Giordano et al demonstrated that there is an increase in CD163+ monocytes in GBM patients compared with healthy donors, which become CD163/FKBP51s+ in cases of residual tumor. 71 Furthermore, CD163/FKBP51s+ monocytes were significantly decreased in individuals with pseudoprogression compared with those with true progression. Similar to monocytes, platelets also infiltrate the tumor microenvironment and are capable of providing angiogenic factors for GBM growth.…”
Section: Cell-based Strategiesmentioning
confidence: 94%
“…70 GBM itself is enriched in monocytes, which differentiate into myeloidderived suppressor cells, nonclassical monocytes, and M2 macrophages. 70,71 These cells can then reenter circulation to exert their global immunosuppressive effects. Importantly, Giordano et al demonstrated that there is an increase in CD163+ monocytes in GBM patients compared with healthy donors, which become CD163/FKBP51s+ in cases of residual tumor.…”
Section: Cell-based Strategiesmentioning
confidence: 99%